Evaluation of the System of Dispensation of Drugs in Intrahospital Services, of a Health Unit of Riobamba - V Rodríguez; T Peñafiel; A Rincón (ESPOCH Congresses, 2021)
Abstract Introduction: In Ecuador, many health institutions have not yet migrated to the Unit Dose Dispensation / Distribution System for Medications, which ensures the correct, safe and rational use of medications. Objective: The medication dispensing process in a Riobamba health unit was evaluated as part of the service quality improvement process. Methodology: Information was collected during three months of investigation, from the in-hospital services of hospitalization, intensive care unit, operating room and emergency. The instruments used for the evaluation corresponded to medical prescriptions, medication and medical device request sheets, medication return record sheets and labeling of boxes. Results: In the medical prescriptions as in the record sheets for the return of evaluated drugs, the main drawback was presented in the writing of the pharmaceutical form and the absence of mandatory data for the identification of the patient. In the total of the registers for the return of medications, the absence of the reason for the return of the medications was identified. The medication dispensing process was considered a critical point within the evaluation, since throughout the review period it was observed that the boxes did not have the minimum required labeling, for the correct identification of the patient. Conclusion: It was concluded that the dispensing system presented critical flaws, such as: deficiencies in the supply of medications, dispensing errors, lack of pharmacotherapeutic follow-up and little participation of the pharmaceutical professional.